From governance to government: The strengthened role of state bureaucracies in forest and agricultural certification - Giessen, Lukas (2016)
Private institutions for third-party (eco-)labelling of food and wood products has been a lively field of empirical research, peaking in the conception of certification as a “non-state market-driven governance system,” which is gaining rule-making authority domestically and internationally as a private governance institution and a transnational regime. Recent findings, however, suggest that state actors also play a decisive role in private certification governance. Questions relating to who within the state, however, so far remain unaddressed. Very recent empirical trends in the fields of timber and palm oil certification in Indonesia suggest that it is distinct public bureaucracies who start reclaiming certification authority through state-led mandatory schemes, challenging the private and transnational certification institutions in support of government-driven international certification regimes. Against this background, the objective of this paper is to substantiate the trend from transnational private to international state-driven governance by analyzing the role of distinct state bureaucracies in the emergence, diffusion, and reshaping of private natural resource governance systems. To achieve these objectives, we develop our propositions by combining insights from political certification studies, regime theory, as well as bureaucratic politics theory. Methodologically, we employ a qualitative case study design on recent developments in forest, timber, and palm oil certification systems in Argentina and Indonesia. Our results substantiate the observation that distinct state actors play a key role in private governance systems and, in the case of Indonesia, even re-claim labelling authority from private institutions by attempting to outcompete them through employing their exclusive regulatory power. The results further indicate a strong, self-interested support from domestic state bureaucracies to state-driven international rather than to transnational certification regimes, supporting the temporary governance hypothesis. We discuss and conclude on our results in light of literatures on private governance, policy sectors as well as international relations theory on the emergence of international and transnational regimes.